2016
DOI: 10.1002/lary.26340
|View full text |Cite
|
Sign up to set email alerts
|

Pantopaque contrast mimicking intracanalicular vestibular schwannoma

Abstract: Pantopaque (iophendylate) is an oily contrast medium historically used during spine imaging. Due to its persistence in the subarachnoid space and the potential to lead to severe arachnoiditis, it is no longer used today. We present a 40-year-old male with new-onset headaches, imbalance, and vertigo. Brain magnetic resonance imaging revealed a 2-mm T1 -hyperintense intracanalicular lesion. Numerous hyperdense foci were scattered throughout the subarachnoid space on computed tomography. Further history revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Mild or severe headache, meningitis, vertigo, imbalance, arachnoidids, hydrocephalus, hypersensitivity have been reported in patients who have intracranial remnants of myodil (4,(9)(10)(11). Although some authors believed that the remnants of pantopaque in the intracranial subarachnoid space should be removed (10), symptomatic treatment and/or periodic follow-up are usually accepted approaches by several authors in minor symptomatic and/or asymptomatic cases (4,8,9,14). Accordingly, in the present cases, no further examinations were carried out in the asymptomatic patient (Case 1), but the patient who complained from headache and backache (Case 2) was advised to visit a neurologist.…”
Section: Discussionmentioning
confidence: 99%
“…Mild or severe headache, meningitis, vertigo, imbalance, arachnoidids, hydrocephalus, hypersensitivity have been reported in patients who have intracranial remnants of myodil (4,(9)(10)(11). Although some authors believed that the remnants of pantopaque in the intracranial subarachnoid space should be removed (10), symptomatic treatment and/or periodic follow-up are usually accepted approaches by several authors in minor symptomatic and/or asymptomatic cases (4,8,9,14). Accordingly, in the present cases, no further examinations were carried out in the asymptomatic patient (Case 1), but the patient who complained from headache and backache (Case 2) was advised to visit a neurologist.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these cases noted pantopaque exposure many decades before presentation, with abnormal imaging noted on CT, MRI, and dental panoramic radiographs. Previous cases have noted the MRI appearance of pantopaque as hyperintense on T1-weighted images and iso- to hypointense on T2-weighted images without gadolinium enhancement [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since its discontinuation, imaging studies with findings suspicious of intradural oil-based contrast have rarely been reported. Although few, there have been documented cases of pantopaque noted on imaging in the spine and intracranially [3][4][5][6]. Many of these cases noted pantopaque exposure many decades before presentation, with abnormal imaging noted on CT, MRI, and dental panoramic radiographs.…”
Section: Introductionmentioning
confidence: 99%